Urban residents' willingness to pay for corn straw burning ban in Henan, China: Application of payment card. (20th August 2018) - Yang, Xiaomei; Cheng, Leilei; Yin, Changbin; Lebailly, Philippe; Azadi, Hossein
Abstract: Urban air pollution generated from straw open burning after the harvest seasons in China has been one of the significant problems interfering with the city's proper functioning. This paper applied contingent valuation in a face to face survey to assess the individual willingness of urban residents in Henan, China to pay for corn straw burning ban to policy makers. Such assessments are important for policy makers to determine the investment and policy instruments for regulating environmental impacts of straw open burning. To investigate the determinants of the stated willingness to pay (WtP) a sample of 1890 urban residents in Henan, China was selected. The study used Tobit model. About 62% of respondents stated that they were willing to pay. The expected WtP was about 76.72 Chinese Yuan (RMB) per person per year for the total respondents and 142.70 RMB per person per year for observations with positive WtP bids. Aggregate value was between 3.41 and 3.90 billion RMB indicating that corn straw burning ban is of considerable economic value to Henan. Results from the study show that the experience of environmental protection, expenditure on protecting health from air pollution, influence of straw burning on respondent's health, life, work, household income, education, job place, and family size were significant variables explaining WtP. The results of the study will be useful for policy makers when making up their mind how much funds should be invested and what kinds of policy instruments could be suitable for banning straw burning. Highlights: We assess the individual willingness to pay (WtP) for corn straw burning ban. The majority of respondents stated that they were willing to pay. The expected WtP was about 76.72 RMB per person per year for the total respondents. The respondent with experience of environmental protection are more willing to pay. The socio-economic characteristics were significant variables explaining WtP.